OP35 Effect of maintenance ustekinumab on corticosteroid-free endoscopic and clinical outcomes in patients with Crohn's Disease - Week 48 analysis of the STARDUST trial. (27th May 2021) - Danese, S; Vermeire, S; D'Haens, G; Panés, J; Dignass, A; Magro, F; Nazar, M; Le Bars, M; Lahaye, M; Ni, L; Bravatà, I; Gaya, D R; et al.
Abstract: Background: The STARDUST study demonstrated that ustekinumab (UST), using either a treat-to-target (T 2 T) or standard of care (SoC) strategy, may induce and maintain endoscopic and clinical response and remission in Crohn's disease (CD). Primary endpoint, safety, and efficacy have been reported previously. 1 Because corticosteroid (CS) sparing is an important aim of CD management, we compared the efficacy of UST T 2 T vs SoC in achieving CS-free clinical remission and endoscopic response. Methods: Adult patients (pts) with moderate–severely active CD who were CDAI 70 responders after 16 weeks (W) of induction, comprising a single dose of UST 6 mg/kg iv followed by UST 90 mg SC at W8, were randomized to either T 2 T or SoC arms. In the T 2 T arm, choice of UST maintenance dosage (q 12 w or q 8 w) was based on endoscopic improvement at W16, followed by clinical and biomarker-directed dose escalation up to q 4 w; in the SoC arm, UST q 12 w or q 8 w dosage was based on EU SmPC. Primary endpoint was endoscopic response (Simple Endoscopic Score in CD [SES-CD] decrease from baseline [BL] ≥50%) at W48. For pts on CS at W16, CS tapering was mandatory. At W48, CS-free clinical remission (CDAI <150 and no CS for ≥30 days) and CS-free endoscopic response (reduction from BL in SES-CD ≥50% and no CS for ≥30 days) were evaluated. Results: Of 500 pts enrolled, 441 achieved a CDAI 70 response at W16 and were randomized to T 2 T (n=220) or SoC (n=221); 79.1% and 87.3%, respectively, completed W48. Among clinical remitters and responders at W16 (start of CS tapering), in both T 2 T and SoC arms more than 70% were still in remission or response at W48 (Figure 1). CS use throughout 48 weeks of treatment is summarized in Table 1. At W48, in T 2 T and SoC arms similar rates were noted for CS-free endoscopic response (33.6% and 28.5%, respectively) and CS-free clinical remission (56.4% and 63.3%, respectively). Notably, in T 2 T and SoC arms the CS-free clinical remission rate among pts on CS at BL was 44.1% and 45.1%, respectively (Figure 2). Among W48 endoscopic responders (T 2 T, n=83; SoC, n=66), CS-free endoscopic response rate was 89.2% and 95.5%, respectively; among W48 clinical remitters (T 2 T, n=135; SoC, n=154), CS-free clinical remission rate was 91.9% and 90.9%, in T 2 T and SoC arms, respectively. Conclusion: Pts treated with UST under T 2 T or SoC strategies achieved similar rates of CS-free clinical remission and endoscopic response over 48 weeks. Overall for pts on CS at BL, UST reduced the need for CS while achieving response/remission. Most (>89%) pts with endoscopic response/clinical remission at W48 were also CS-free responders/remitters. Reference: Danese S, et al. United European Gastroenterol J . 2020;8:1264–1265 (Abstract LB11).